Distinct Genotype of Hantavirus Infection in Rodents in Jiangxi Province, China, in 2020–2021 - Xuefei Deng; Yun Xie; Shanshan Du; Xiaoxia Huang; Qin Wang; Aqian Li; Chuan Li; Sheng Ding; Lina Sun; Wei Wu; Hao Li; Chun Xie; et al. (Zoonoses)
Hantavirus causes hemorrhagic fever with renal syndrome, thus posing a major threat to human health in Jiangxi Province, China. Both Hantaan virus (HTNV) and Seoul virus (SEOV) have been found to be endemic in the province. Rodents were trapped from Gaoan Anyi and Tonggu counties in Jiangxi Province in 2020–2021. Hantavirus specific antibodies in the blood and RNA in the lung samples from the captured mammals were detected and analyzed. A total of 889 small mammals from seven species were collected. Positive detection was observed for hantavirus antibodies in 9.8% (87/889), SEOV RNA in 1% (9/889) and HTNV RNA in 2.6% (23/889). The difference in detection rates between regions was significant. Phylogenetic analysis of the obtained partial sequences of M and S segments revealed that two distinct genotypes of HTNV and three genotypes of SEOV were co-circulating in the captured mammals, with a regionally specific distribution. Multiple distinct genotypes of hantavirus are co-circulating in the province. Further studies in broader areas remain needed to reveal the diversity of hantaviruses.